The Nexus between Public Expenditure and Economic Growth: Array - Mokoena, Sipho K.; Rachidi, Mamoloko; Ngwakwe, Collins C. (EuroEconomica, 2020)
Research on the nexus between government expenditure and economic growth produces mixed results from different countries. Objective. The objective of this paper is to test if a causal relationship exists between government expenditure and economic growth in South Africa. Prior work: the paper relied on testing the applicability of Wagner’s and Keynesian theories on public expenditure and economic growth with data from South Africa. Approach. Data on South Africa’s government expenditure and economic growth for 1961 – 2018 were used and the Granger causality Wald test was used to analyse the causality. Result. Neither Wager’s nor Keynesian hypothesis was proven within the limit of the fifty-eight years’ data used. This is because the results show no significant causal relationship from either side of economic growth and public expenditure. Implication. Policy makers should pay attention on how to channel government expenditure and the gains from economic growth to improve citizens’ ability to increase their productive capital. Further researchers should expand the time series coverage to go beyond 1961 to check for new results; a regional panel data for Southern Africa is also recommended for further research. Value. This paper produces a new test of Wagner’s and Keynesian hypothesis by merging data from the pre-democratic with the democratic period of South Africa and applied a combination of ADF, co-integration, VAR and Granger Causality analysis.